2015
DOI: 10.1016/j.tecto.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

The geological signature of a slab tear below the Aegean

Abstract: Mediterranean Highlights-Rotation of Hellenides is coeval with granite migration -Migration of granitoids signs a slab tear in the Cyclades -HT domes and a left-lateral gradient of extension also sign the tear AbstractIn this paper we explore the geology of the Aegean region in the Miocene to identify the geological signature of a first-order slab tear observed in all tomographic models. From 15 to 8 Ma, the tear is associated, spatially and timely, with a fast clockwise rotation of the External Hellenides, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
110
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(136 citation statements)
references
References 158 publications
(258 reference statements)
7
110
2
Order By: Relevance
“…In addition, the westward emplacement of syn-tectonic intrusions from the Menderes massif to the Cyclades in the Miocene (figure 11), associated with an increase of the mantle source component of these magmas [Stouraiti et al, 2010;Jolivet et al, 2015], can be correlated with this slab tear. Indeed, as shown by analog and numerical modeling [Funiciello et al, 2003Piromallo et al, 2006;Faccenda and Capitanio, 2012;Sternai et al, 2014], slab tearing-related asthenospheric flow displays a significant toroidal component that could progressively heat the base of the stretched lithosphere inducing partial melting.…”
Section: Modulation Of Magmatic Evolution By Slab Tearing and Mantle mentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, the westward emplacement of syn-tectonic intrusions from the Menderes massif to the Cyclades in the Miocene (figure 11), associated with an increase of the mantle source component of these magmas [Stouraiti et al, 2010;Jolivet et al, 2015], can be correlated with this slab tear. Indeed, as shown by analog and numerical modeling [Funiciello et al, 2003Piromallo et al, 2006;Faccenda and Capitanio, 2012;Sternai et al, 2014], slab tearing-related asthenospheric flow displays a significant toroidal component that could progressively heat the base of the stretched lithosphere inducing partial melting.…”
Section: Modulation Of Magmatic Evolution By Slab Tearing and Mantle mentioning
confidence: 95%
“…Recently, Jolivet et al [2015] proposed instead a left-lateral transfer zone, accommodated as a gradient of finite extension across a large part of the central Aegean domain.…”
mentioning
confidence: 99%
“…Jolivet et al, 2013;Philippon et al, 2011), or normal faulting in an overall extensional regime (Gautier et al, 1999;Hinsbergen and Schmid, 2012) including vertical axis rotations in the footwall (Malandri et al, 2017). Field evi-dence is controversial, as there seems that there is neither support for a major detachment (Brun et al, 2016;Jolivet et al, 2015;Philippon et al, 2014) nor is strike-slip faulting observed on Paros, where the Mid-Cycladic Lineament might be exposed (Malandri et al, 2017;Walcott and White, 1998a). Additional complexity is added due to interaction of slab roll-back with westward migration of the Anatolian Plate since ∼ 11 Ma Ring et al, 2010).…”
Section: E-w Shorteningmentioning
confidence: 99%
“…Strike-slip-dominated shear zones bordering the western and eastern margins of the Menderes MCC have been recognised as NE-trending and crustal-scale transfer zones, which lie parallel to the regional extension direction (Brun & Sokoutis, 2010;Gessner et al, 2016;Jolivet et al, 2015;Ring et al, 1999). The shear zones on the western margin are inferred to have been active since Late Cretaceous and are comprised of major NE-trending dextral and sinistral fault sets accompanied by NW-and E-W-trending faults (İzmir-Balıkesir Transfer Zone, (Erkül, Helvacı, & Sözbilir, 2005); İzmir shear zone, (Brun & Sokoutis, 2010); the West Anatolia Transfer Zone, (Gessner, Gallardo, Markwitz, Ring, & Thomson, 2013)).…”
Section: Timing Of the Gerni Shear Zonementioning
confidence: 99%